2022
DOI: 10.3389/fpsyg.2022.940718
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ dissatisfaction during the COVID-19 pandemic: Factors contributing to a desire to leave the profession

Abstract: IntroductionThe COVID-19 pandemic required more responsibilities from teachers, including implementing prevention strategies, changes in school policies, and managing their own mental health, which yielded higher dissatisfaction in the field.MethodsA cross-sectional web survey was conducted among educators to collect information on their experiences teaching during the COVID-19 pandemic throughout the 2020–2021 academic year. Qualtrics, an online survey platform, fielded the survey from May 6 to June 8, 2021 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…In Hypothesis 1, we assumed COVID-19-related losses in the school climate. Based on previous COVID-19 studies reporting increased teacher stress associated with lower perceived school climate (e.g., Brion & Kiral, 2022; Gillani et al, 2022; Trinidad, 2021), limited adaptive teaching (e.g., Letzel et al, 2020), lower school satisfaction (e.g., Haller & Novita, 2021; Kirsch et al, 2021), and decreased extracurricular activities (e.g., Finnerty et al, 2021; Ilari et al, 2022; LaForge-MacKenzie et al, 2022), a loss in teachers’ school climate ratings is plausible. However, we did not observe this in our study, and one possible explanation could be the way in which school climate was measured, at least in terms of the two dimensions of satisfaction with school quality (SSQ) and school as a living space (SLS).…”
Section: Discussionmentioning
confidence: 99%
“…In Hypothesis 1, we assumed COVID-19-related losses in the school climate. Based on previous COVID-19 studies reporting increased teacher stress associated with lower perceived school climate (e.g., Brion & Kiral, 2022; Gillani et al, 2022; Trinidad, 2021), limited adaptive teaching (e.g., Letzel et al, 2020), lower school satisfaction (e.g., Haller & Novita, 2021; Kirsch et al, 2021), and decreased extracurricular activities (e.g., Finnerty et al, 2021; Ilari et al, 2022; LaForge-MacKenzie et al, 2022), a loss in teachers’ school climate ratings is plausible. However, we did not observe this in our study, and one possible explanation could be the way in which school climate was measured, at least in terms of the two dimensions of satisfaction with school quality (SSQ) and school as a living space (SLS).…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review also revealed a lack of assessment of organizational culture and supports; both play a key role in promoting health in the workplace, and a lack of organizational support can increase job stressors, leading to burnout 61 . Teacher retention efforts might include employee wellness programs to help educators manage and reduce their stress, which is inextricably linked to mental health.…”
Section: Discussionmentioning
confidence: 99%
“…60 This systematic review also revealed a lack of assessment of organizational culture and supports; both play a key role in promoting health in the workplace, and a lack of organizational support can increase job stressors, leading to burnout. 61 Teacher retention efforts might include employee wellness programs to help educators manage and reduce their stress, which is inextricably linked to mental health. Based on this review, few studies have examined the mental health outcomes of employee health and well-being programs; yet staff that perceive their workplace as being supportive of health and wellbeing tend to have better mental and physical health outcomes than those that do not feel a similar level of support.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing the effectiveness of employee health and well‐being programs in school settings is critically important, particularly given the latest trends of teacher and staff burnout and desire to leave the profession 53 . Only 4 school‐based studies were identified for inclusion in the employee health and well‐being review in this special issue 21 .…”
Section: Future Researchmentioning
confidence: 99%